Doll bones - Black, Holly (New York : Margaret K. McElderry Books, 2013)
Zach, Alice, and Poppy, friends from a Pennsylvania middle school who have long enjoyed acting out imaginary adventures with dolls and action figures, embark on a real-life quest to Ohio to bury a doll made from the ashes of a dead girl.
OBOB 2018-2019
840L
All Secondary
V
5.4
Keywords: Adventure and adventurers -- Fiction; Friendship -- Fiction; Dolls -- Fiction; Ghosts -- Fiction; Family problems -- Fiction; Adventure and adventurers -- Fiction; Family problems -- Fiction; Newbery Honor book; Ghost stories